Information System Development for Reading and Writing Qur'an at Tarbiyah and Teacher Training Faculty of UIN Sunan Kalijaga - Nur Hidayat; Kasyful Albab Al Musthofa; Adhi Setiyawan (Edulab: Majalah Ilmiah Laboratorium Pendidikan, 2023)
Some Postgraduate and Doctoral Alumni of UIN Sunan Kalijaga, Faculty of Tarbiyah Sciences do not yet have Quranic literacy skills, so the Faculty of Tarbiyah and Teacher Training held standardization for students who will graduate by adding conditions to be able to take part in the munaqasah session by passing the Quran Literacy Exam. This research uses the plomp method and the assure method because it can simplify the stages systematically. The results of this quranic literacy examination research graduates from postgraduate or doctoral from the faculty of tarbiyah science and teacher training can read and write the Quran all and make student output better than the previous year’.